Simple Artificial Intelligence Tools for School Libraries in Nigeria - Nwafor-Orizu, Obianuju E.; Okonkwo, Ifeyinwa N.; Obiozor-Ekeze, Roseline Nkechi (Communicate: Journal of Library and Information Science, 2025)
Globally, the application of Artificial Intelligence in libraries, also known as Library 5.0, is shifting traditional operations toward more automated, user-centered models. However, in Nigeria, the adoption of such systems remains limited, probably due to infrastructural challenges, cost constraints, low levels of digital literacy and awareness. In this context, the concept of “simple AI tools” becomes particularly relevant as the first steps school librarians can take. These tools include easy-to-use and cost-effective AI-powered applications that can be deployed with minimal technical expertise. This research is targeted at identifying the simple but basic and effective AI tools which school librarians can start with.in Nigeria. It is based on comprehensive literature review. Ten tools were specified alongside their functions and features for easy and practical application. It is concluded that aggressive adoption of AI tools in school libraries should be the priority of all stakeholders.